KISTA DUKTUS TIROGLOSUS - Susanto, Ezra Aditya; Suaryana, Sp.B, dr. Sang Nyoman (E-Jurnal Medika Udayana; vol 2 no 10 (2013):e-jurnal medika udayana)
Thyroglosal duct cyst is a cyst that had formed from duct thyroglosal who settled along the groove decreased thyroid gland, from the foramen caecum to the superior portion of the thyroid gland in the front of the trachea. There are two theories that can cause cystic duct thyroglosal recurrent throat infection which will stimulate the rest of that tract epithelial degeneration and cystic duct obstruction thyroglosal will result in accumulation of secretions that form cysts. Another theory given thyroglosal duct located between several lymph nodes in the neck, if it happens often inflammation, the ductal epithelium also inflamed, forming a cyst. Diagnosis can usually be made from the history and physical examination of the neck as a whole. Always palpation of the thyroid gland during a physical examination. If the gland can not be felt, ultrasound, thyroid scan or CT scan can help. Initial management, if there is an infection, overcome the infection with antibiotics first and then warm compresses. After the infection is resolved, the next step is the treatment of cystic duct which Sistrunk procedure is more commonly used. Thyroglosal duct cyst had a good prognosis, the recurrence rate about 5% by Sistrunk procedure. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Thyroglosal duct cyst, thyroid gland, Sistrunk